Antiskid matt film and preparation method thereof
By using a four-layer anti-slip matte film, a rough surface is constructed using modified polypropylene and composite modified anti-slip particles, which solves the problem of poor anti-slip performance of matte film and achieves a stable stacking effect of matte film in anti-slip scenarios.
Patent Information
- Application Number
- CN202511492086.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-20
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-10-20
AI Technical Summary
Existing biaxially oriented polypropylene matte film has a high coefficient of friction when laminated with plastic woven bags, but it is prone to causing packaging to slide and become unstable when containing granular products, thus limiting its application in anti-slip performance scenarios.
The anti-slip matte film adopts a four-layer structure, consisting of an anti-adhesion layer, a support layer, a connecting layer, and a matte layer. It uses modified polypropylene and composite modified anti-slip particles to construct a composite rough structure, increasing the surface friction coefficient. It uses isocyanate groups to modify polypropylene to improve adhesion and flexibility, and uses N-(2-aminoethyl)-3-aminopropyltrimethoxysilane to modify silicon carbide fibers and corundum to form a complementary rough surface.
It significantly increases the anti-slip properties of the matte film, preventing packaging from sliding and collapsing when stacked, and improves the surface friction and stability of the film material.
Smart Images

Figure CN120963168A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of matte films, specifically to an anti-slip matte film and its preparation method. Background Technology
[0002] Biaxially oriented polypropylene matte film, when combined with plastic woven bags, is widely used in the packaging of food, chemical products, and fertilizers. Although the coefficient of friction of biaxially oriented polypropylene matte film is higher than that of ordinary glossy film, it is still prone to slippage and unstable stacking when granular products are stacked, which limits its application in scenarios requiring anti-slip performance.
[0003] Therefore, developing an anti-slip matte film and its preparation method has significant practical application value. Summary of the Invention
[0004] In order to overcome the above-mentioned technical problems, the present invention aims to provide an anti-slip matte film and its preparation method, which solves the problem that the existing matte film has poor anti-slip performance and is prone to packaging slippage and unstable stacking.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] In the first aspect, this application provides an anti-slip matte film, which is composed of a four-layer structure formed by sequentially stacking and co-extruded an anti-adhesion layer, a support layer, a connecting layer and a matte layer;
[0007] The anti-blocking layer comprises the following components in parts by weight: 94-98 parts of polypropylene and 2-6 parts of anti-blocking masterbatch;
[0008] The support layer comprises the following components in parts by weight: 97-99 parts of polypropylene and 1-3 parts of antistatic masterbatch;
[0009] The component of the connecting layer is polypropylene;
[0010] The matte layer comprises the following components by weight: 60-80 parts of matte masterbatch, 10-20 parts of copolymer polyolefin, 15-20 parts of modified polypropylene, 7-15 parts of composite modified anti-slip particles, and 5-10 parts of C5 petroleum resin.
[0011] The modified polypropylene is prepared by the following steps:
[0012] Step a1: Isophorone diisocyanate, p-tert-butylcatechol, and dibutyltin dilaurate are added to a three-necked flask equipped with a stirrer, thermometer, and constant pressure dropping funnel. The mixture is stirred for 10-20 min at a temperature of 20-25℃ and a stirring rate of 200-300 r / min. Then, the temperature is raised to 40-45℃ and 2-hydroxyethyl acrylate is added dropwise while stirring, with the dropping rate controlled at 1-3 drops / s. After the addition is complete, the mixture is stirred for another 2-3 h. After the reaction is complete, the reaction product is cooled to room temperature to obtain the isocyanate alkenyl compound.
[0013] Step a2: Polypropylene, dicumyl peroxide, isocyanate alkenyl compound, and xylene are added to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Nitrogen gas is introduced for protection. The mixture is stirred at 20-25℃ and 200-300 r / min for 1-2 hours. Then, the temperature is raised to 120-130℃ and the stirring is continued for 3-4 hours. After the reaction is completed, the reaction product is cooled to room temperature and then poured into ethyl acetate. After standing for 30-60 minutes to precipitate, it is then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at 60-65℃ for 3-4 hours to obtain isocyanate alkenyl grafted polypropylene.
[0014] Step a3: Isocyanate-based grafted polypropylene, isophorone diisocyanate, melamine, dibutyltin dilaurate, dimethyl sulfoxide, and xylene are added to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Nitrogen gas is introduced for protection. The mixture is stirred and reacted at 20-25℃ and 200-300 r / min for 1-2 hours. Then, the temperature is raised to 80-90℃ and the stirring is continued for 3-4 hours. After the reaction is completed, the reaction product is poured into anhydrous acetone while hot. The mixture is then allowed to stand for 30-60 minutes to precipitate. After that, it is vacuum filtered, and the filter cake is placed in a vacuum drying oven and dried at 40-45℃ for 6-8 hours to obtain modified polypropylene.
[0015] In a preferred embodiment of the present invention, the thickness of the anti-adhesion layer is 1.0-1.5 μm.
[0016] In a preferred embodiment of the present invention, the thickness of the support layer is 10-15 μm.
[0017] In a preferred embodiment of the present invention, the thickness of the connecting layer is 0.5-1.0 μm.
[0018] In a preferred embodiment of the present invention, the thickness of the matting layer is 2.0-3.0 μm.
[0019] In a preferred embodiment of the present invention, the ratio of isophorone diisocyanate, p-tert-butylcatechol, dibutyltin dilaurate and 2-hydroxyethyl acrylate in step a1 is 10 mmol: 0.01-0.02 g: 0.03-0.05 g: 10 mmol.
[0020] In a preferred embodiment of the present invention, the ratio of polypropylene, dicumyl peroxide, isocyanate alkenyl compound and xylene in step a2 is 3g:0.3-0.5g:0.02-0.04g:30-40mL.
[0021] In a preferred embodiment of the present invention, the polypropylene in step a2 is homopolymer polypropylene HB28F.
[0022] In a preferred embodiment of the present invention, the ratio of the amount of isocyanate-alkenyl-grafted polypropylene, isophorone diisocyanate, melamine, dibutyltin dilaurate, dimethyl sulfoxide and xylene in step a3 is 20g:10mmol:10mmol:0.1-0.2g:40-50mL:80-100mL.
[0023] In a preferred embodiment of the present invention, the composite modified anti-slip particles are prepared by the following steps:
[0024] Silicon carbide fiber, corundum, and ethanol solution were added to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred for 10-20 minutes at a temperature of 20-25℃ and a stirring rate of 200-300 r / min. The pH was then adjusted to 8-9 with ammonia water, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane was added. The mixture was stirred for another 20-30 minutes, and then the temperature was raised to 60-70℃ and the mixture was stirred for another 3-4 hours. After the reaction was completed, the product was cooled to room temperature and then vacuum filtered. The filter cake was washed 2-3 times with distilled water and then placed in a vacuum drying oven and dried at a temperature of 60-65℃ for 3-4 hours to obtain composite modified anti-slip particles.
[0025] In a preferred embodiment of the present invention, the ratio of silicon carbide fiber, corundum, ethanol solution and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 3g:2.5-5.1g:60-70mL:1.3-4.5g.
[0026] In a preferred embodiment of the present invention, the silicon carbide fiber is a KD-II type silicon carbide fiber.
[0027] In a preferred embodiment of the present invention, the average particle size of the corundum is 500 mesh.
[0028] In a preferred embodiment of the present invention, the volume fraction of the ethanol solution is 85-90%.
[0029] In a preferred embodiment of the present invention, the ammonia water has a mass fraction of 20-22%.
[0030] Secondly, this application provides a method for preparing an anti-slip matte film, comprising the following steps:
[0031] Step 1: The raw materials for the anti-adhesion layer, support layer, connecting layer and matte layer are fed into different extruders and melt-extruded at a temperature of 220-250℃ and a screw speed of 40-120r / min. The extruded melts are filtered through a 320-mesh filter and then extruded in sequence through a four-layer die to obtain a composite film.
[0032] Step 2: The composite film is subjected to longitudinal stretching, transverse stretching and corona treatment to obtain a master roll film. The master roll film is then subjected to aging treatment and then cut to obtain an anti-slip matte film.
[0033] In a preferred embodiment of the present invention, the temperature is controlled at 90-135°C and the longitudinal stretching ratio is 4.5-5.5 during the longitudinal stretching process.
[0034] In a preferred embodiment of the present invention, the temperature is controlled at 150-175°C and the transverse stretching ratio is 8-10 during the transverse stretching process.
[0035] In a preferred embodiment of the present invention, the corona treatment power is 22-30 Wmin / m. 2 .
[0036] Compared with the prior art, the beneficial effects of the present invention are:
[0037] A non-slip matte film and its preparation method are disclosed. The method involves melting and extruding the raw materials for an anti-adhesion layer, a support layer, a connecting layer, and a matte layer separately, then sequentially merging and extruding them to obtain a composite film. The composite film is then subjected to longitudinal stretching, transverse stretching, and corona treatment to obtain a master roll film. The master roll film undergoes aging treatment and is subsequently cut to obtain the non-slip matte film. This preparation method utilizes modified polypropylene and composite modified anti-slip particles as modifying materials to modify the bottom matte layer of the non-slip matte film. Modified polypropylene enhances the adhesion and flexibility of the non-slip matte film, while composite modified anti-slip particles construct a composite rough structure. The synergistic effect of these two materials significantly increases the surface friction coefficient, thereby endowing the non-slip matte film with excellent anti-slip properties, effectively preventing packaging slippage and stack collapse.
[0038] In the preparation of the anti-slip matte film, a modified polypropylene was first prepared. This was achieved through a reaction between isophorone diisocyanate and 2-hydroxyethyl acrylate. One isocyanate group on the isophorone diisocyanate reacts with a hydroxyl group on the 2-hydroxyethyl acrylate, yielding an isocyanate-alkenyl compound containing both isocyanate groups and alkenyl groups. Subsequently, polypropylene was initiated by dicumyl peroxide to form free radicals, which then reacted with the alkenyl groups on the isocyanate-alkenyl compound, introducing the isocyanate groups into the molecular structure of the polypropylene, resulting in isocyanate-alkenyl-grafted polypropylene. This isocyanate-alkenyl-grafted polypropylene was then treated with isophorone diisocyanate and melamine, where melamine has multiple amino groups. The amino group can react with isocyanate groups grafted onto isocyanate-alkenyl polypropylene, thereby introducing a large number of amino groups. Further reaction with isophorone diisocyanate introduces even more isocyanate groups, and also increases the degree of cross-linking between polypropylene molecules, resulting in modified polypropylene. This modified polypropylene contains a large number of isocyanate groups in its molecular structure. The introduction of isocyanate groups increases the polarity of the polypropylene molecular chain, improves the surface energy of the membrane and its compatibility with other additives, and also enhances the adhesion and flexibility of the polypropylene. When subjected to frictional forces, the membrane not only slightly adheres to the external object but also undergoes slight deformation with the anti-slip particles, increasing the "interlocking" area of the contact surface and thus improving friction.
[0039] In the process of preparing the anti-slip matte film, a composite modified anti-slip particle was also prepared. N-(2-aminoethyl)-3-aminopropyltrimethoxysilane was used to modify silicon carbide fibers and corundum. The siloxane on N-(2-aminoethyl)-3-aminopropyltrimethoxysilane was hydrolyzed into silanol, which was then grafted onto the surface of the silicon carbide fibers and corundum. Simultaneously, a large number of amino and secondary amine groups were introduced to obtain the composite modified anti-slip particle. This composite modified anti-slip particle utilizes the needle-like structure of the silicon carbide fibers and the granular structure of the corundum to form a complementary rough surface, constructing a "micro-convex-fiber interwoven" composite rough structure on the film surface, significantly increasing the surface friction coefficient. Furthermore, after modification, the amino and secondary amine groups can react with the isocyanate groups in the modified polypropylene to achieve chemical anchoring, ensuring the particles remain stably on the film surface and preventing the anti-slip performance from decreasing due to particle shedding during use. Attached Figure Description
[0040] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to the accompanying drawings.
[0041] Figure 1 This is a schematic diagram of the anti-slip matte film of the present invention.
[0042] Figure 2This is a schematic diagram showing the friction coefficient test results of the anti-slip matte film in Examples 2-4 and Comparative Examples 1-3 of the present invention. Detailed Implementation
[0043] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0044] Example 1:
[0045] Please see Figure 1 As shown, this embodiment is an anti-slip matte film, which consists of a four-layer structure formed by sequentially stacking and co-extruded an anti-adhesion layer, a support layer, a connecting layer and a matte layer;
[0046] The thickness of the anti-adhesion layer is 1.2 μm, the thickness of the support layer is 13 μm, the thickness of the connecting layer is 0.8 μm, and the thickness of the matting layer is 2.5 μm.
[0047] Example 2:
[0048] This embodiment describes a method for preparing an anti-slip matte film, comprising the following steps:
[0049] Step S1: 10 mmol of isophorone diisocyanate, 0.01 g of p-tert-butylcatechol and 0.03 g of dibutyltin dilaurate were added to a three-necked flask equipped with a stirrer, thermometer and constant pressure dropping funnel. The mixture was stirred for 10 min at 20 °C and a stirring rate of 200 r / min. Then, 10 mmol of 2-hydroxyethyl acrylate was added dropwise while stirring at 40 °C, with the dropping rate controlled at 1 drop / s. After the addition was completed, the mixture was stirred for another 2 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain the isocyanate alkenyl compound.
[0050] Step S2: Add 3g of homopolymer polypropylene HB28F, 0.3g of dicumyl peroxide, 0.02g of isocyanate alkenyl compound and 30mL of xylene to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 20℃ and 200r / min for 1h. Then raise the temperature to 120℃ and continue stirring for 3h. After the reaction is completed, cool the reaction product to room temperature and pour it into ethyl acetate. Let it stand for 30min to precipitate, then vacuum filter it. Place the filter cake in a vacuum drying oven and dry it at 60℃ for 3h to obtain isocyanate alkenyl grafted polypropylene.
[0051] Step S3: 20g of isocyanate-based alkenyl-grafted polypropylene, 10mmol of isophorone diisocyanate, 10mmol of melamine, 0.1g of dibutyltin dilaurate, 40mL of dimethyl sulfoxide, and 80mL of xylene were added to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred at 20℃ and 200r / min for 1h. Then, the temperature was raised to 80℃ and the stirring was continued for 3h. After the reaction was completed, the reaction product was poured into anhydrous acetone while hot, and then allowed to stand for 30min to precipitate. After that, it was vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 40℃ for 6h to obtain modified polypropylene.
[0052] Step S4: Add 3g of KD-II type silicon carbide fiber, 2.5g of diamond with an average particle size of 500 mesh, and 60mL of 85% ethanol solution to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir for 10min at 20℃ and 200r / min. Then adjust the pH to 8 with 20% ammonia water. Add 1.3g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and continue stirring for 20min. Then raise the temperature to 60℃ and continue stirring for 3h. After the reaction is complete, cool the reaction product to room temperature, then vacuum filter. Wash the filter cake twice with distilled water and then place it in a vacuum drying oven and dry at 60℃ for 3h to obtain composite modified anti-slip particles.
[0053] Step S5: Weigh the raw materials for the anti-blocking layer, support layer, connecting layer and matte layer according to their respective weight proportions, and set aside for later use;
[0054] The anti-blocking layer comprises the following components by weight: 94 parts polypropylene and 2 parts anti-blocking masterbatch; wherein the polypropylene is homopolymer polypropylene HB28F; and the anti-blocking masterbatch is Suzhou Constance AB 6018 PP.
[0055] The support layer comprises the following components by weight: 97 parts polypropylene and 1 part antistatic masterbatch; wherein the polypropylene is polypropylene T28F; and the antistatic masterbatch is Suzhou Constance AT 4030 PP-HC.
[0056] The connecting layer is composed of polypropylene; the polypropylene is Yanshan Petrochemical F5005B.
[0057] The matte layer comprises the following components by weight: 60 parts matte masterbatch, 10 parts copolymer polyolefin, 15 parts modified polypropylene, 7 parts composite modified anti-slip particles, and 5 parts C5 petroleum resin; wherein the matte masterbatch is Best Technology DUL8260PP; the copolymer polyolefin is EVA DQDJ-1868 from Japan Unica; and the C5 petroleum resin is Shanghai Jinshan C5 petroleum resin SJ1304.
[0058] Step S6: The raw materials for the anti-adhesion layer, support layer, connecting layer and matte layer are fed into different extruders and melt-extruded at a temperature of 220℃ and a screw speed of 40r / min. The extruded melts are filtered through a 320-mesh filter and then extruded sequentially in a four-layer die to obtain a composite film.
[0059] Step S7: The composite film is subjected to longitudinal stretching, transverse stretching, and corona treatment to obtain a master roll film. The master roll film is then subjected to aging treatment and slit to obtain an anti-slip matte film. During the longitudinal stretching process, the temperature is controlled at 90℃ and the longitudinal stretching ratio is 4.5. During the transverse stretching process, the temperature is controlled at 150℃ and the transverse stretching ratio is 8. The corona treatment power is 22 Wmin / m. 2 .
[0060] Example 3:
[0061] This embodiment describes a method for preparing an anti-slip matte film, comprising the following steps:
[0062] Step S1: 10 mmol of isophorone diisocyanate, 0.015 g of p-tert-butylcatechol and 0.04 g of dibutyltin dilaurate were added to a three-necked flask equipped with a stirrer, thermometer and constant pressure dropping funnel. The mixture was stirred at 22 °C and 250 r / min for 15 min. Then, the temperature was raised to 42 °C and 10 mmol of 2-hydroxyethyl acrylate was added dropwise while stirring, with the dropping rate controlled at 2 drops / s. After the addition was completed, the mixture was stirred for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain the isocyanate alkenyl compound.
[0063] Step S2: 3g of homopolymer polypropylene HB28F, 0.4g of dicumyl peroxide, 0.03g of isocyanate alkenyl compound, and 35mL of xylene were added to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred at 22℃ and 250r / min for 1.5h. Then, the temperature was raised to 125℃ and the stirring was continued for 3.5h. After the reaction was completed, the reaction product was cooled to room temperature and then poured into ethyl acetate. After standing for 45min to precipitate, it was vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at 62℃ for 3.5h to obtain isocyanate alkenyl grafted polypropylene.
[0064] Step S3: 20g of isocyanate-based alkenyl-grafted polypropylene, 10mmol of isophorone diisocyanate, 10mmol of melamine, 0.15g of dibutyltin dilaurate, 45mL of dimethyl sulfoxide, and 90mL of xylene were added to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred at 22℃ and 250r / min for 1.5h. Then, the temperature was raised to 85℃ and the mixture was stirred for another 3.5h. After the reaction was completed, the reaction product was poured into anhydrous acetone while hot, and then allowed to stand for 45min to precipitate. After that, the mixture was vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 42℃ for 7h to obtain modified polypropylene.
[0065] Step S4: Add 3g of KD-II type silicon carbide fiber, 3.8g of 500-mesh corundum, and 65mL of 88% ethanol solution to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir at 22℃ and 250r / min for 15min. Then adjust the pH to 8.5 with 21% ammonia solution. Add 2.9g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and continue stirring for 25min. Then raise the temperature to 65℃ and continue stirring for 3.5h. After the reaction is complete, cool the reaction product to room temperature, then vacuum filter. Wash the filter cake twice with distilled water and then place it in a vacuum drying oven and dry at 62℃ for 3.5h to obtain composite modified anti-slip particles.
[0066] Step S5: Weigh the raw materials for the anti-blocking layer, support layer, connecting layer and matte layer according to their respective weight proportions, and set aside for later use;
[0067] The anti-blocking layer comprises the following components by weight: 96 parts polypropylene and 4 parts anti-blocking masterbatch; wherein the polypropylene is homopolymer polypropylene HB28F; and the anti-blocking masterbatch is Suzhou Constance AB 6018 PP.
[0068] The support layer comprises the following components by weight: 98 parts polypropylene and 2 parts antistatic masterbatch; wherein the polypropylene is polypropylene T28F; and the antistatic masterbatch is Suzhou Constance AT 4030 PP-HC.
[0069] The connecting layer is composed of polypropylene; the polypropylene is Yanshan Petrochemical F5005B.
[0070] The matte layer comprises the following components by weight: 70 parts matte masterbatch, 15 parts copolymer polyolefin, 18 parts modified polypropylene, 11 parts composite modified anti-slip particles, and 8 parts C5 petroleum resin; wherein the matte masterbatch is Best Technology DUL8260PP; the copolymer polyolefin is EVA DQDJ-1868 from Japan Unica; and the C5 petroleum resin is Shanghai Jinshan C5 petroleum resin SJ1304.
[0071] Step S6: The raw materials for the anti-adhesion layer, support layer, connecting layer and matte layer are fed into different extruders and melt-extruded at a temperature of 235℃ and a screw speed of 80r / min. The extruded melts are filtered through a 320-mesh filter and then extruded sequentially in a four-layer die to obtain a composite film.
[0072] Step S7: The composite film is subjected to longitudinal stretching, transverse stretching, and corona treatment to obtain a master roll film. The master roll film is then subjected to aging treatment and cut to obtain an anti-slip matte film. During the longitudinal stretching process, the temperature is controlled at 110℃ and the longitudinal stretching ratio is 5.0; during the transverse stretching process, the temperature is controlled at 160℃ and the transverse stretching ratio is 9; the corona treatment power is 26 Wmin / m. 2 .
[0073] Example 4:
[0074] This embodiment describes a method for preparing an anti-slip matte film, comprising the following steps:
[0075] Step S1: 10 mmol of isophorone diisocyanate, 0.02 g of p-tert-butylcatechol and 0.05 g of dibutyltin dilaurate were added to a three-necked flask equipped with a stirrer, thermometer and constant pressure dropping funnel. The mixture was stirred at 25 °C and 300 r / min for 20 min. Then, the temperature was raised to 45 °C and 10 mmol of 2-hydroxyethyl acrylate was added dropwise while stirring, with the dropping rate controlled at 3 drops / s. After the addition was completed, the mixture was stirred for 3 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain the isocyanate alkenyl compound.
[0076] Step S2: Add 3g of homopolymer polypropylene HB28F, 0.5g of dicumyl peroxide, 0.04g of isocyanate alkenyl compound and 40mL of xylene to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 300r / min for 2h. Then raise the temperature to 130℃ and continue stirring for 4h. After the reaction is completed, cool the reaction product to room temperature and pour it into ethyl acetate. Let it stand for 60min to precipitate, then filter under vacuum. Place the filter cake in a vacuum drying oven and dry at 65℃ for 4h to obtain isocyanate alkenyl grafted polypropylene.
[0077] Step S3: 20g of isocyanate-based alkenyl-grafted polypropylene, 10mmol of isophorone diisocyanate, 10mmol of melamine, 0.2g of dibutyltin dilaurate, 50mL of dimethyl sulfoxide, and 100mL of xylene were added to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred at 25℃ and a stirring rate of 300r / min for 2h. Then, the temperature was raised to 90℃ and the stirring was continued for 4h. After the reaction was completed, the reaction product was poured into anhydrous acetone while hot, and then allowed to stand for 60min to precipitate. After that, it was vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 45℃ for 8h to obtain modified polypropylene.
[0078] Step S4: Add 3g of KD-II type silicon carbide fiber, 5.1g of diamond with an average particle size of 500 mesh, and 70mL of 90% ethanol solution to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 300r / min for 20min. Then adjust the pH to 9 with 22% ammonia water. Add 4.5g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and continue stirring for 30min. Then raise the temperature to 70℃ and continue stirring for 4h. After the reaction is complete, cool the reaction product to room temperature and then filter under vacuum. Wash the filter cake three times with distilled water and then place it in a vacuum drying oven and dry at 65℃ for 4h to obtain composite modified anti-slip particles.
[0079] Step S5: Weigh the raw materials for the anti-blocking layer, support layer, connecting layer and matte layer according to their respective weight proportions, and set aside for later use;
[0080] The anti-blocking layer comprises the following components by weight: 98 parts polypropylene and 6 parts anti-blocking masterbatch; wherein the polypropylene is homopolymer polypropylene HB28F; and the anti-blocking masterbatch is Suzhou Constance AB 6018 PP.
[0081] The support layer comprises the following components by weight: 99 parts polypropylene and 3 parts antistatic masterbatch; wherein the polypropylene is polypropylene T28F; and the antistatic masterbatch is Suzhou Constance AT 4030 PP-HC.
[0082] The connecting layer is composed of polypropylene; the polypropylene is Dushanzi Petrochemical TF1007.
[0083] The matte layer comprises the following components by weight: 80 parts matte masterbatch, 20 parts copolymer polyolefin, 20 parts modified polypropylene, 15 parts composite modified anti-slip particles, and 10 parts C5 petroleum resin; wherein the matte masterbatch is Best Technology DUL8260PP; the copolymer polyolefin is EVA DQDJ-1868 from Japan Unica; and the C5 petroleum resin is Shanghai Jinshan C5 petroleum resin SJ1304.
[0084] Step S6: The raw materials for the anti-adhesion layer, support layer, connecting layer and matte layer are fed into different extruders and melt-extruded at a temperature of 250℃ and a screw speed of 120r / min. The extruded melts are filtered through a 320-mesh filter and then extruded sequentially in a four-layer die to obtain a composite film.
[0085] Step S7: The composite film is subjected to longitudinal stretching, transverse stretching, and corona treatment to obtain a master roll film. The master roll film is then subjected to aging treatment and cut to obtain an anti-slip matte film. During the longitudinal stretching process, the temperature is controlled at 135℃ and the longitudinal stretching ratio is 5.5. During the transverse stretching process, the temperature is controlled at 175℃ and the transverse stretching ratio is 10. The corona treatment power is 30Wmin / m. 2 .
[0086] Comparative Example 1:
[0087] This comparative example illustrates a method for preparing an anti-slip matte film, comprising the following steps:
[0088] Step S1: Weigh the raw materials for the anti-blocking layer, support layer, connecting layer and matte layer according to their respective weight proportions, and set aside for later use;
[0089] The anti-blocking layer comprises the following components by weight: 98 parts polypropylene and 6 parts anti-blocking masterbatch; wherein the polypropylene is homopolymer polypropylene HB28F; and the anti-blocking masterbatch is Suzhou Constance AB 6018 PP.
[0090] The support layer comprises the following components by weight: 99 parts polypropylene and 3 parts antistatic masterbatch; wherein the polypropylene is polypropylene T28F; and the antistatic masterbatch is Suzhou Constance AT 4030 PP-HC.
[0091] The connecting layer is composed of polypropylene; the polypropylene is Dushanzi Petrochemical TF1007.
[0092] The matte layer comprises the following components by weight: 80 parts matte masterbatch, 20 parts copolymer polyolefin, 20 parts polypropylene, and 10 parts C5 petroleum resin; wherein the matte masterbatch is Best Technology DUL8260PP; the copolymer polyolefin is EVA DQDJ-1868 from Japan; the polypropylene is homopolymer polypropylene HB28F; and the C5 petroleum resin is Shanghai Jinshan C5 petroleum resin SJ1304.
[0093] Step S2: The raw materials for the anti-adhesion layer, support layer, connecting layer and matte layer are fed into different extruders and melt-extruded at a temperature of 250℃ and a screw speed of 120r / min. The extruded melts are filtered through a 320-mesh filter and then extruded sequentially in a four-layer die to obtain a composite film.
[0094] Step S3: The composite film is subjected to longitudinal stretching, transverse stretching, and corona treatment to obtain a master roll film. The master roll film is then subjected to aging treatment and cut to obtain an anti-slip matte film. During the longitudinal stretching process, the temperature is controlled at 135℃ and the longitudinal stretching ratio is 5.5; during the transverse stretching process, the temperature is controlled at 175℃ and the transverse stretching ratio is 10; the corona treatment power is 30Wmin / m. 2 .
[0095] Comparative Example 2:
[0096] This comparative example illustrates a method for preparing an anti-slip matte film, comprising the following steps:
[0097] Step S1: Add 3g of KD-II type silicon carbide fiber, 5.1g of diamond with an average particle size of 500 mesh, and 70mL of 90% ethanol solution to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 300r / min for 20min. Then adjust the pH to 9 with 22% ammonia water. Add 4.5g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and continue stirring for 30min. Then raise the temperature to 70℃ and continue stirring for 4h. After the reaction is completed, cool the reaction product to room temperature and then filter under vacuum. Wash the filter cake three times with distilled water and then place it in a vacuum drying oven and dry at 65℃ for 4h to obtain composite modified anti-slip particles.
[0098] Step S2: Weigh the raw materials for the anti-blocking layer, support layer, connecting layer and matte layer according to their respective weight proportions, and set aside for later use;
[0099] The anti-blocking layer comprises the following components by weight: 98 parts polypropylene and 6 parts anti-blocking masterbatch; wherein the polypropylene is homopolymer polypropylene HB28F; and the anti-blocking masterbatch is Suzhou Constance AB 6018 PP.
[0100] The support layer comprises the following components by weight: 99 parts polypropylene and 3 parts antistatic masterbatch; wherein the polypropylene is polypropylene T28F; and the antistatic masterbatch is Suzhou Constance AT 4030 PP-HC.
[0101] The connecting layer is composed of polypropylene; the polypropylene is Dushanzi Petrochemical TF1007.
[0102] The matte layer comprises the following components by weight: 80 parts matte masterbatch, 20 parts copolymer polyolefin, 20 parts polypropylene, 15 parts composite modified anti-slip particles, and 10 parts C5 petroleum resin; wherein the matte masterbatch is Best Technology DUL8260PP; the copolymer polyolefin is EVA DQDJ-1868 from Japan; the polypropylene is homopolymer polypropylene HB28F; and the C5 petroleum resin is Shanghai Jinshan C5 petroleum resin SJ1304.
[0103] Step S3: The raw materials for the anti-adhesion layer, support layer, connecting layer and matte layer are fed into different extruders and melt-extruded at a temperature of 250℃ and a screw speed of 120r / min. The extruded melts are filtered through a 320-mesh filter and then extruded sequentially in a four-layer die to obtain a composite film.
[0104] Step S4: The composite film is subjected to longitudinal stretching, transverse stretching, and corona treatment to obtain a master roll film. The master roll film is then subjected to aging treatment and slit to obtain an anti-slip matte film. During the longitudinal stretching process, the temperature is controlled at 135℃ and the longitudinal stretching ratio is 5.5; during the transverse stretching process, the temperature is controlled at 175℃ and the transverse stretching ratio is 10; the corona treatment power is 30Wmin / m. 2 .
[0105] Comparative Example 3:
[0106] This comparative example illustrates a method for preparing an anti-slip matte film, comprising the following steps:
[0107] Step S1: 10 mmol of isophorone diisocyanate, 0.02 g of p-tert-butylcatechol and 0.05 g of dibutyltin dilaurate were added to a three-necked flask equipped with a stirrer, thermometer and constant pressure dropping funnel. The mixture was stirred at 25 °C and 300 r / min for 20 min. Then, the temperature was raised to 45 °C and 10 mmol of 2-hydroxyethyl acrylate was added dropwise while stirring, with the dropping rate controlled at 3 drops / s. After the addition was completed, the mixture was stirred for 3 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain the isocyanate alkenyl compound.
[0108] Step S2: Add 3g of homopolymer polypropylene HB28F, 0.5g of dicumyl peroxide, 0.04g of isocyanate alkenyl compound and 40mL of xylene to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 300r / min for 2h. Then raise the temperature to 130℃ and continue stirring for 4h. After the reaction is completed, cool the reaction product to room temperature and pour it into ethyl acetate. Let it stand for 60min to precipitate, then filter under vacuum. Place the filter cake in a vacuum drying oven and dry at 65℃ for 4h to obtain isocyanate alkenyl grafted polypropylene.
[0109] Step S3: 20g of isocyanate-based alkenyl-grafted polypropylene, 10mmol of isophorone diisocyanate, 10mmol of melamine, 0.2g of dibutyltin dilaurate, 50mL of dimethyl sulfoxide, and 100mL of xylene were added to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred at 25℃ and a stirring rate of 300r / min for 2h. Then, the temperature was raised to 90℃ and the stirring was continued for 4h. After the reaction was completed, the reaction product was poured into anhydrous acetone while hot, and then allowed to stand for 60min to precipitate. After that, it was vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 45℃ for 8h to obtain modified polypropylene.
[0110] Step S4: Weigh the raw materials for the anti-blocking layer, support layer, connecting layer and matte layer according to their respective weight proportions, and set aside for later use;
[0111] The anti-blocking layer comprises the following components by weight: 98 parts polypropylene and 6 parts anti-blocking masterbatch; wherein the polypropylene is homopolymer polypropylene HB28F; and the anti-blocking masterbatch is Suzhou Constance AB 6018 PP.
[0112] The support layer comprises the following components by weight: 99 parts polypropylene and 3 parts antistatic masterbatch; wherein the polypropylene is polypropylene T28F; and the antistatic masterbatch is Suzhou Constance AT 4030 PP-HC.
[0113] The connecting layer is composed of polypropylene; the polypropylene is Dushanzi Petrochemical TF1007.
[0114] The matte layer comprises the following components by weight: 80 parts matte masterbatch, 20 parts copolyolefin, 20 parts modified polypropylene, and 10 parts C5 petroleum resin; wherein the matte masterbatch is Best Technology DUL8260PP; the copolyolefin is EVA DQDJ-1868 from Japan Unica; and the C5 petroleum resin is Shanghai Jinshan C5 petroleum resin SJ1304.
[0115] Step S5: The raw materials for the anti-adhesion layer, support layer, connecting layer and matte layer are fed into different extruders and melt-extruded at a temperature of 250℃ and a screw speed of 120r / min. The extruded melts are filtered through a 320-mesh filter and then extruded sequentially in a four-layer die to obtain a composite film.
[0116] Step S6: The composite film is subjected to longitudinal stretching, transverse stretching, and corona treatment to obtain a master roll film. The master roll film is then subjected to aging treatment and cut to obtain an anti-slip matte film. During the longitudinal stretching process, the temperature is controlled at 135℃ and the longitudinal stretching ratio is 5.5. During the transverse stretching process, the temperature is controlled at 175℃ and the transverse stretching ratio is 10. The corona treatment power is 30Wmin / m. 2 .
[0117] Performance testing
[0118] The anti-slip matte films of Examples 2-4 and Comparative Examples 1-3 were tested for their coefficient of friction according to GB / T 10006-2021. The test location was the matte layer of the anti-slip matte film. The test results are as follows: Figure 2 As shown.
[0119] See Figure 2 As shown, based on the comparison between Examples 2-4 and Comparative Examples 1-3, it can be seen that using modified polypropylene and adding composite modified anti-slip particles can significantly improve the coefficient of friction of the anti-slip matte film, thereby significantly improving its anti-slip effect.
[0120] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0121] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.
Claims
1. An anti-slip type matting film, characterized by, The four-layer structure is formed by co-extrusion of the anti-adhesion layer, the support layer, the connecting layer and the matt layer in sequence; The anti-adhesion layer comprises the following components by weight: 94-98 parts of polypropylene and 2-6 parts of anti-adhesion masterbatch; The support layer comprises the following components by weight: 97-99 parts of polypropylene and 1-3 parts of anti-static masterbatch; The connecting layer is made of polypropylene; The matt layer comprises the following components by weight: 60-80 parts of matt masterbatch, 10-20 parts of copolymerized polyolefin, 15-20 parts of modified polypropylene, 7-15 parts of composite modified anti-slip particles and 5-10 parts of C5 petroleum resin; The modified polypropylene is prepared by the following steps: Step a1: isophorone diisocyanate, p-tert-butyl catechol and dibutyltin dilaurate are stirred to react, then 2-hydroxyethyl acrylate is added dropwise for further stirring, the reaction product is cooled after the reaction, and an isocyanate alkenyl compound is obtained; Step a2: polypropylene, dicumyl peroxide, the isocyanate alkenyl compound and xylene are stirred to react, the reaction product is cooled after the reaction, then poured into ethyl acetate, and then precipitated after standing, vacuum filtration, drying the filter cake, and an isocyanate alkenyl grafted polypropylene is obtained; Step a3: the isocyanate alkenyl grafted polypropylene, isophorone diisocyanate, melamine, dibutyltin dilaurate, dimethyl sulfoxide and xylene are stirred to react, the reaction product is poured into anhydrous acetone while hot after the reaction, then precipitated after standing, vacuum filtration, and drying the filter cake, and a modified polypropylene is obtained.
2. The anti-slip type matting film according to claim 1, wherein The thickness of the anti-adhesion layer is 1.0-1.5 μm, the thickness of the support layer is 10-15 μm, the thickness of the connecting layer is 0.5-1.0 μm, and the thickness of the matt layer is 2.0-3.0 μm.
3. The anti-slip type matting film according to claim 1, wherein The amount ratio of the isophorone diisocyanate, p-tert-butyl catechol, dibutyltin dilaurate and 2-hydroxyethyl acrylate in step a1 is 10 mmol:0.01-0.02 g:0.03-0.05 g:10 mmol.
4. The anti-slip type matting film according to claim 1, wherein The amount ratio of the polypropylene, dicumyl peroxide, the isocyanate alkenyl compound and xylene in step a2 is 3 g:0.3-0.5 g:0.02-0.04 g:30-40 mL; the polypropylene is homopolymer polypropylene HB28F.
5. The anti-slip type matting film according to claim 1, wherein The amount ratio of the isocyanate alkenyl grafted polypropylene, isophorone diisocyanate, melamine, dibutyltin dilaurate, dimethyl sulfoxide and xylene in step a3 is 20 g:10 mmol:10 mmol:0.1-0.2 g:40-50 mL:80-100 mL.
6. The anti-slip type matting film according to claim 1, wherein The composite modified anti-slip particles are prepared by the following steps: The silicon carbide fiber, diamond and ethanol solution are stirred to react, then the pH is adjusted with ammonia water, then N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is added for further stirring, the reaction product is cooled after the reaction, then vacuum filtration, and the filter cake is washed and dried to obtain the composite modified anti-slip particles.
7. The anti-slip type matting film according to claim 6, wherein The silicon carbide fiber, the corundum, the ethanol solution and the N-(2-aminoethyl)-3-aminopropyl trimethoxysilane are in a ratio of 3g:2.5-5.1g:60-70mL:1.3-4.5g.
8. The anti-slip type matting film according to claim 6, wherein The silicon carbide fiber is KD-Ⅱ type silicon carbide fiber. The average particle size of the corundum is 500 mesh. The volume fraction of the ethanol solution is 85-90%. The mass fraction of the ammonia water is 20-22%.
9. A method for producing the anti-slip type matting film according to any one of claims 1 to 8, characterized by, The method comprises the following steps: Step one: raw materials of the anti-adhesion layer, the support layer, the connecting layer and the matt layer are respectively put into different extruders, and then melted and extruded under the condition that the temperature is 220-250℃ and the screw rotation speed is 40-120r / min, the melted bodies respectively extruded are filtered through a 320-mesh filter, and then are converged and extruded in sequence in a four-layer structure die to obtain a composite film; Step two: the composite film is longitudinally stretched, transversely stretched and subjected to corona treatment to obtain a mother roll film, the mother roll film is subjected to aging treatment, and then is cut to obtain the anti-skid matt film.
10. The method for preparing an anti-slip matte film according to claim 9, characterized in that, The temperature control during the longitudinal stretching is 90-135 DEG C, the longitudinal stretching ratio is 4.5-5.5; the temperature control during the transverse stretching is 150-175 DEG C, the transverse stretching ratio is 8-10; the corona treatment power is 22-30 Wmin / m 2 .
Citation Information
Patent Citations
Anti-fog type ultraviolet light curing polyacrylate copolymer preparation method
CN102924662A
Polystyrene foam plastic modified acrylic emulsion and preparation method thereof
CN106279545A
Solvent-free composite polypropylene matte film with controllable glossiness and preparation method thereof
CN119101474A
Decorative sheet
JP2003103736A
Super wear-resistant BOPP thin film and preparation method therefor
WO2022165985A1